Estresse de metais na produtividade de compostos oriundos do metabolismo secundário de martianthus leucocephalus (mart. Ex benth.) J.f.b. Pastore - Jesus, Daniel da Silva de (2016)
Lamiaceae species have been widely studied due to their antioxidant, antimicrobial and antiviral properties. There is scientific interest in developing technologies for the enhancement of production systems of medicinal plants, given that the low concentration of bioactive compounds is a major obstacle to their economic exploitation. Works with some species have shown that traces metals such as Cd, Cu and Zn, act as abiotic elicitors, directly influencing in the production of bioactive substances. Martianthus leucocephalus (Mart. Ex Benth.) J.F.B. Pastore produces rich essential oil in isobornyl formate with high antimicrobial activity. This work aimed to evaluate the effect of Cd, Cu and Zn stress, on the species through growth, minerals accumulation, essential oil content and its major components, phenolic content and antioxidant enzymes. Furthermore, the phytoremediation potential of this species was observed in the presence of the tested metals. When applied in high concentrations all metals caused sharp reduction in the M. leucocephalus growth, however, was observed that Zn stress caused an increase in the content of volatile compounds. Plant exposure of to milder metals concentrations caused less growth reduction and nutritional unbalance M. leucocephalus. In this case, Cd stress stimulate higher production of volatile compounds. No metal treatment alters the essential oils quality. Cd, Cu and Zn was accumulated in higher concentration in the roots, demonstrating the potential of this species to phytostabilization in contaminated environments. The Cd stress caused an increase in total phenolics concentration, while the peroxidases activity and lipid peroxidation was higher in metals stressed plants.